An anti‐interferon activity shared by paramyxovirus C proteins: Inhibition of Toll‐like receptor 7/9‐dependent alpha interferon induction. Issue 1 (20th November 2013) - Yamaguchi, Mayu; Kitagawa, Yoshinori; Zhou, Min; Itoh, Masae; Gotoh, Bin
Abstract : Paramyxovirus C protein targets the host interferon (IFN) system for virus immune evasion. To identify its unknown anti‐IFN activity, we examined the effect of Sendai virus C protein on activation of the IFN‐α promoter via various signaling pathways. This study uncovers a novel ability of C protein to block Toll‐like receptor (TLR) 7‐ and TLR9‐dependent IFN‐α induction, which is specific to plasmacytoid dendritic cells. C protein interacts with a serine/threonine kinase IKKα and inhibits phosphorylation of IRF7. This anti‐IFN activity of C protein is shared across genera of the Paramyxovirinae, and thus appears to play an important role in paramyxovirus immune evasion. Abstract : We identified a novel anti‐interferon activity of paramyxovirus C protein. C protein inhibits TLR7/9‐dependent alpha interferon induction. C protein binds to IKKα and inhibits phosphorylation of IRF7. The novel anti‐interferon activity of C protein is shared across genera.